2017
DOI: 10.1002/mnfr.201700438
|View full text |Cite
|
Sign up to set email alerts
|

Chromium supplementation for adjuvant treatment of type 2 diabetes mellitus: Results from a pooled analysis

Abstract: Scope:We conducted a pooled analysis of randomized controlled trials to evaluate the effects of chromium supplementation on clinically relevant metabolic biomarkers in type 2 diabetes mellitus (T2DM) patients. Methods and results: Electronic searches were conducted and the bibliographies of located articles were searched, and 28 studies were suitable for statistical pooling. Endpoints were calculated as weighted mean differences (WMDs) with 95% confidence intervals (CIs) by using fixed-effects or random-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 64 publications
0
18
1
Order By: Relevance
“…Although chromium supplementation was associated with decrease of FBG levels in diabetic patients [1], in the present study CrPic supplementation failed to affect the blood glucose levels while decreased HOMA-IR values. Considering chemistry and pharmacology of chromium, it was a safe nutrient for supplementation in T2DM [22].…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Although chromium supplementation was associated with decrease of FBG levels in diabetic patients [1], in the present study CrPic supplementation failed to affect the blood glucose levels while decreased HOMA-IR values. Considering chemistry and pharmacology of chromium, it was a safe nutrient for supplementation in T2DM [22].…”
Section: Discussioncontrasting
confidence: 76%
“…Type 2 diabetes mellitus (T2DM) remains a serious public health problem, with high rates of morbidity and mortality in low-or middle-income countries [1]. The prevalence of T2DM is increasing at an alarming rate, so that the number of Iranian adults suffering from diabetes was more than four millions in 2011 and has been raised by 35% over the past years [2].…”
Section: Introductionmentioning
confidence: 99%
“…The use of omega-3 s for prevention of cardiovascular events has been controversial however the most recent meta-analysis of 127,477 participants demonstrates lower risk of cardiovascular events including AMI, CHD death, and total CVD death [157] with marine omega-3 supplementation. Coenzyme Q10 may be beneficial in heart failure [158] T2D: Zinc [159], curcumin [160], Coenzyme Q10 [161], probiotics [162,163], and chromium [164] have been demonstrated to have beneficial effects on glycemic control and cardiovascular risk factors in meta-analyses in people with T2D…”
Section: Integrative Medicinementioning
confidence: 99%
“…[9] Very recent pooled analysis study conducted by Huang et al suggested that patients with T2D supplemented chromium picolinate or chromium chloride had lower levels of fasting serum glucose. [10] However, earlier in 2016, Costello et al , in a meta-analysis evaluated the later randomized clinical trials, concluded that there is still little reason to recommend chromium supplements to achieve significant improvements in glycemic control. [11] Besides, oral chromium picolinate was found to improved lipid metabolism in obese rats,[12] and in humans.…”
Section: Introductionmentioning
confidence: 99%